Evaluation of the Perceptions and Approaches of Theology Faculty Students in Türkiye in the Context of Migration and Racism - Aydin, Selcuk; Sahin, Abdurrahim (Österreichisches Religionspädagogisches Forum, 2025)
The intensification of global migration in recent years has caused an increase in racism and exclusionary discourses in many host societies. This study examines how religious education shapes theology students’ views on racism and migration in Türkiye. Findings from in-depth interviews suggest that religious education promotes inclusive attitudes and serves as a moral barrier against racism. However, its influence is constrained by nationalist narratives, cultural anxieties, and economic concerns. While religious teachings initially foster solidarity, primarily through the notion of religious brotherhood, their effect weakens when faced with real-life integration challenges. The study highlights both the potential and limitations of religious education in countering racism.